First report of natural hybridisation between members of Teucrium subsect. Simplicipilosa and subsect. Polium: Teucrium × murcigerum (Lamiaceae), a new hybrid from southeastern Iberian Peninsula - de Juan-Pérez, Alba; Martínez-Azorín, Mario; Crespo, Manuel B.; Alonso-Vargas, María Ángeles (Phytotaxa, 2023)
A new nothospecies, Teucrium × murcigerum, is described which comes from the hybridisation between two species of section Polium: Teucrium murcicum (subsect. Polium) and Teucrium lanigerum (subsect. Simplicipilosa), both endemic to SE Iberian Peninsula. This appears to be the first report of natural intersubsectional hybridisation between T. subsect. Polium and subsect. Simplicipilosa. A morphological description is reported, emphasizing the main diagnostic characters which allow separation from its parental taxa. Additionally, data on its biology, ecology and distribution are also presented, as well as relationships to other related nothospecies produced by its parentals.